National Association of Colleges and Employers Job Outlook 2023 (2022)
The Job Outlook survey is a forecast of hiring intentions of employers as they relate to new college graduates. Eachyear, the National Association of Colleges and Employers (NACE) surveys its employer members about their hiringplans and other employment-related issues to project the market for new college graduates for the current class andto assess a variety of conditions that may influence that market.Data for the Job Outlook 2023 survey were collected from August 3, 2022, through September 16, 2022.Of the 246 total respondents, 150 were NACE employer members, representing 17.4% of eligible memberrespondents. The Job Outlook 2023 survey was also distributed to nonmember companies, from which anadditional 96 responses were received.Of the total that responded, 7.3% are from New England, 10.6% are from the Mideast, 11.8% are from the Southwest,13.4% are from the Plains, 17.1% are from the Southeast, 17.5% are from the Rocky Mountain/Far West, and 22.4% arefrom the Great Lakes. For additional information about the respondents, see the Appendix.Data are calculated based on the number of respondents to each specific question. Totals may not equal 100% dueto rounding.NACE expects to provide a formal job market update during the 2022-23 academic year. Based on data collected inFebruary and March, the Job Outlook 2023 Spring Update report will give NACE members a final update on hiring for2022-23 graduates. Results will be available in early April.